Target-based visibility assessment on building envelopes: Applications to PV and cultural-heritage values - Lingfors, David; Johansson, Tim; Widén, Joakim; Broström, Tor (Energy and buildings, 2019)
•A novel approach for visibility assessment on buildings is proposed.•The new method is based on the target’s instead of the observerâ;;s perspective.•Different definitions of the vantage area are evaluated.•Visibility is combined with PV and cultural-heritage values in two case studies.•The method can be used for city planning when visibility is important. [Display omitted] Solar energy applications have, in recent years, become a common element in the urban landscape, especially on roofs and facades. However, it is important that the integration of solar energy in the built environment do not distort the fabric or expression of the existing building envelope, not at least in areas of high cultural-heritage values. The aesthetics depend, to a large extent, on how visible the new technology, such as photovoltaic (PV) panels, is. This paper describes a method for visibility assessment of building envelopes. It is referred to as target-based as it, in contrast to previously reported methods, bases the assessment from the perspective of the building envelope itself, rather than possible vantage points on the ground. The method was evaluated for two Swedish cities; Stockholm and Visby. In Stockholm, each building was evaluated based on its cultural-heritage values, solar irradiation and visibility. Deploying PV only on the roofs with the lowest cultural-heritage values, with insolation  > 900  kWh/m2, and with no visibility from ground, results in a total PV yield of up to 2% of the total electricity demand. In Visby, various definitions of the vantage area were evaluated, from which the building envelope can be seen. It was found that the choice of vantage area greatly impacts the solar energy potential. If the vantage area is defined by the public domain, i.e., streets and other public open spaces, the non-visible roof area doubles compared to if all ground/terrain defines it. Compared to previous studies, the use of a vantage area, instead of discrete vantage points, seems to result in higher visibility of the roofs.